2019
DOI: 10.33160/yam.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maximum Air Temperature on Ambulance Transports Owing to Heat Stroke During Spring and Summer in Tottori Prefecture, Japan: A Time-stratified Case-crossover Analysis

Abstract: Background The frequency and intensity of hot weather have increased. In Japan, there have been many studies of the relationship between ambulance transports owing to heat stroke (ATHS) and high air temperature in the summer season. However, there have been very few reports focusing on ATHS in spring. Therefore, we investigated the effect of the maximum air temperature on ATHS not only in summer but also in spring, to help with development of effective measures to prevent heat stroke. Methods We obtained daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(31 reference statements)
0
13
1
Order By: Relevance
“…We only used the air temperature as a meteorological indicator in the case-crossover analysis and did not include relative humidity. Our previous study did not find an association with heat stroke transport [12] and we also found no association with heat stroke severity in the present study. One of the reasons is that the relative humidity in the target area remained extremely high in July and August.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…We only used the air temperature as a meteorological indicator in the case-crossover analysis and did not include relative humidity. Our previous study did not find an association with heat stroke transport [12] and we also found no association with heat stroke severity in the present study. One of the reasons is that the relative humidity in the target area remained extremely high in July and August.…”
Section: Discussioncontrasting
confidence: 80%
“…transports for heat strokes and were able to quantify the risk by temperature [12]. However, to date, most studies have focused on the maximum temperature.…”
Section: Study Design and Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of elderly people among all heat stroke patients has been high in Tottori Prefecture [3]. The current study found that this trend was amplified in 2020.…”
Section: Discussionmentioning
confidence: 51%
“…The maximum temperature on the day when heatstroke occurred (case period) was compared to the maximum temperature on another day when heatstroke did not occur (reference period). The reference period was selected on the same day of the week, in the same year and month as the case period, using the time strati cation method, referring to examples from previous studies [23,37]. The analysis was performed using R version 1.3.1093.…”
Section: ( )mentioning
confidence: 99%